Relation between Serum Lipids and Thyroid Hormones in Hypothyroidism Patients (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Hypothyroidism is a condition that occurs as a result of a malfunction in the thyroid glandsthat leads to a decrease in the secretion of their main hormones. Thyroid hormones are known to be havean important role in the regulating metabolism of lipids; thus, any impaired in the thyroid function causesa significant change in the levels of lipid. Objective: To evaluate the changes occurs for lipid levels inhypothyroidism patients and determine the correlation between lipids parameters and some thyroid hormones.Materials and Methods: The study included 45 healthy control subjects and 52 hypothyroidism patientswho visited private doctors’ clinics in Basra, Iraq. Thyroid hormones and serum lipids were measured forboth healthy subjects and hypothyroidism patients. Results: The study indicates an increase in the thyroidstimulating hormone (TSH) values for hypothyroidism patients as compared to the healthy control groupwhile there is a slightly difference in the values of each of triiodothyronine (T3) and thyroxine (T4) betweenthe two groups. There is a significant increase in the mean values of all lipids except for high densitylipoprotein (HDL) in the hypothyroidism patients compared to that in healthy control subjects. The studypresents that there is a positive correlation between TSH and all lipid parameters except for HDL whichgives negative relation (r = - 0.20). There is a moderate correlation between TSH and non-HDL (r = 0.42)while the other lipids appear weak correlation (TC(r=0.14), TG (r=0.19). LDL (0.16), VLDL (0.17), andLDL/HDL (0.17)). There is no correlation between T4 and TC (r = 0.03), LDL (r = 0.07). non-HDL (r =0.04), and LDL/HDL (r = 0.06), HDL (r = - 0.02) while TG and VLDL appears weak correlation (r = -0.11 to each one of them). Conclusions: The study found that the abnormal change in the levels of lipidsduring hypothyroidism may increase the likelihood for occurrence of arteriosclerosis and the emergence ofcardiovascular disease in hypothyroidism patients. There is a moderate positive relationship between TSHand non-HDL levels, as this indicates that non-HDL should be added to lipid profile tests as evidence ofmeasuring cardiac risk in patients with hypothyroidism
Keywords: hypothyroidism, atherosclerosis, T4, TSH, non-HDL.